A 'time and motion' evaluation of automated dispensing machines in the emergency department. Issue 2 (May 2016) - Roman, Cristina; Poole, Susan; Walker, Catherine; Smit, De Villiers; Dooley, Michael J.
Summary: Background: There has been limited assessment of the impact that automated medication dispensing machines have on the medication administration process, particularly in Australian emergency departments. The aim of this study is to examine the change in medication retrieval times, number of medications retrieved and staff perceptions before and after the installation of automated dispensing machines in an Australian emergency and trauma centre. Methods: A time and motion method recorded the time taken and number of medications retrieved from the medication room by emergency department staff, before and after the installation of two automated dispensing machines. Surveys were administered to staff members to elicit the perceived impact on clinical practice, utilising 5-point Likert scales. Results: A total of 954 medication retrievals (1030 medications) were recorded in the pre-implementation period and 842 (991 medications) in the post-implementation period. The mean time taken to retrieve any medication was significantly longer in the post-implementation period (+5.7 s; p < 0.01). For schedules 2, 3, 4 or unscheduled medications, the mean time increased by 26.9 s ( p < 0.01), but decreased by 36.1 s ( p < 0.01) for schedule 8 or 11 medications. The mean number of medications per retrieval increased slightly in the post implementation period (+0.10; p < 0.01). Staff perceptions were that automated dispensing machines improve knowledge of medications on imprest ( p = 0.03) and reduced medication retrieval time ( p < 0.01). Conclusions: This study found that the medication retrieval process was slower with automated dispensing machines for Schedules 2, 3, 4 and unscheduled medications, but quicker for Schedule 8 and 11 medications in an Australian emergency and trauma centre. Although retrieving medications took slightly longer overall, staff believed automated dispensing machines save time.